536TiPINSIGHT 2: Tepotinib plus osimertinib in patients with EGFR-mutant NSCLC having acquired resistance to EGFR TKIs due to MET-amplification: A phase II trial in progress study. (24th November 2019) - Yang, J C-H; Ellers-Lenz, B; Straub, J; Johne, A; Wu, Y-L
Abstract: Background: MET amplification (METamp) is a resistance mechanism to EGFR tyrosine kinase inhibitors (TKIs) occurring via over activation of downstream signaling pathways such as PI3K and MAPK. METamp occurs in ≈10% of patients receiving erlotinib, gefitinib, afatinib, or icotinib, and is the most common resistance mechanism to osimertinib in phase III trials, occurring in ≈19% of patients. Tepotinib, an oral once daily potent and selective MET inhibitor, is associated with improved survival in combination with gefitinib in patients with EGFR-mutant MET-amplified NSCLC with EGFR TKI resistance compared with standard chemotherapy in the INSIGHT study (NCT01982955): investigator-reported progression free survival (PFS) was 21.2 vs 4.2 months (HR 0.13; 90% CI 0.04, 0.43) and overall survival, (OS) was 37.3 vs. 13.1 months (HR 0.08; 90% CI 0.01, 0.51). Trial design: INSIGHT 2 (NCT03940703) is a global single-arm, open-label, phase II trial of tepotinib in patients with advanced (stage IIIB/IV) NSCLC with resistance to 1 st –3 rd generation EGFR TKIs driven by METamp. Eligibility criteria include patients aged ≥18 years with advanced EGFR-mutant NSCLC and known T790M status, having acquired resistance to EGFR TKIs, and are METamp positive by plasma 'liquid' biopsy, with an ECOG PS of 0 or 1 and normal organ function. Prior immunotherapy is permitted but prior MET pathway-targeted therapy is not. Tepotinib (500 mg orally once daily) in combination with osimertinib (80 mg once daily) will be administered until disease progression, unacceptable toxicity, or withdrawal of consent. An initial safety run-in will comprise 6 patients (endpoint; dose-limiting toxicities); anticipated full enrollment is 90 patients. The primary endpoint is objective response rate (ORR) by independent review committee (RECIST v1.1). Secondary objectives include investigator-assessed ORR, duration of response, disease control, PFS, OS, pharmacokinetics, health-related quality of life, tolerability, and safety (NCI-CTCAE v5.0). Recruitment is ongoing and approximately 80 study sites in 17 countries in Europe, Asia, and North America are expected to participate in this study. Clinical trial identification: NCT03940703. Legal entity responsible for the study: Merck Healthcare KGaA. Funding: Merck Healthcare KGaA. Disclosure: J.C-H. Yang: Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Eli Lilly; Honoraria (self), Advisory / Consultancy: Bayer; Honoraria (self), Advisory / Consultancy: Roche/Genentech/Chugai; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Merck Serono; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy: Merrimack; Honoraria (self), Advisory / Consultancy: Yuhan Pharmaceuticals; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Ono Pharmaceutical; Honoraria (self), Advisory / Consultancy: Daiichi Sankyo ; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Takeda Oncology; Honoraria (self), Advisory / Consultancy: Blueprint Medicines; Honoraria (self), Advisory / Consultancy: Hansoh Pharmaceuticals. B. Ellers-Lenz: Full / Part-time employment: Merck Healthcare KGaA. J. Straub: Full / Part-time employment: Merck Healthcare KGaA. A. Johne: Full / Part-time employment: Merck Healthcare KGaA. Y-L. Wu: Honoraria (self), Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Advisory / Consultancy: Merck; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self): Eli Lilly; Honoraria (self): Pfizer; Honoraria (self): Pierre Fabre; Honoraria (self): Sanofi.